Republic of Croatia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The first analysis focuses on external stability, an important issue in view of Croatia's external imbalances and the requirements of the IMF's 2007 Decision on Bilateral Surveillance. The paper shows that the real exchange rate is broadly in line with economic fundamentals and that external debt dynamics are sustainable as long as macroeconomic policies remain strong. The second analysis finds significant inefficiencies in Croatia's social spending. It also discusses several reform measures to reduce inefficiencies in public spending and generate budgetary savings to reduce the general government deficit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet